Identification and characterisation of endo-l,4-β-glucanase family members in Hevea brasiliensis - Chung, H.H; Chow, K.S; Thompson, C.; Mollison, E. (Malaysian Rubber Board, 2015)
In order to study wood formation in Hevea brasiliensis, endo-l,4-β-glucanase (EGase) was selected for molecular genetic analysis. EGase sequences were isolated from bark, leaf and latex transcriptomes (clone RRIM 928). Altogether, 22 sequences were obtained from the bark transcriptome while 14 and 8 sequences were obtained from leaf and latex transcriptomes, respectively. Based on multiple sequence alignment, only twelve sequences encoded full protein open reading frames while the others contained partial proteins. Translation of twelve EGase sequences (designated HbEgl-12) produced peptide sequences ranging from 494-622 amino acids. Based on protein motif conservation and phylogenetic analysis, these EGases were separated into three classes, A, B and C. Expression of EGase was found to be generally low in latex, bark and leaves.